Answer:
The graph of the function is shown below.
Step-by-step explanation:
The given function is
![f(x)=x^2+2x-6](https://tex.z-dn.net/?f=f%28x%29%3Dx%5E2%2B2x-6)
![f(x)=(x^2+2x)-6](https://tex.z-dn.net/?f=f%28x%29%3D%28x%5E2%2B2x%29-6)
If an expression is defined as
, then we need to add
to make it perfect square.
Here, b=2 so add and subtract 1 in the above parenthesis.
![f(x)=(x^2+2x+1-1)-6](https://tex.z-dn.net/?f=f%28x%29%3D%28x%5E2%2B2x%2B1-1%29-6)
![f(x)=(x^2+2x+1)-1-6](https://tex.z-dn.net/?f=f%28x%29%3D%28x%5E2%2B2x%2B1%29-1-6)
.... (1)
The vertex form of a parabola is
.... (2)
where, (h,k) is vertex.
On comparing (1) and (2) we get
![h=-1,k=-7](https://tex.z-dn.net/?f=h%3D-1%2Ck%3D-7)
So, the vertex of the parabola is (-1,-7) and axis of symmetry is x=-1.
The x-intercepts of the equation is
![0=(x+1)^2-7](https://tex.z-dn.net/?f=0%3D%28x%2B1%29%5E2-7)
![7=(x+1)^2](https://tex.z-dn.net/?f=7%3D%28x%2B1%29%5E2)
![\pm \sqrt{7}=x+1](https://tex.z-dn.net/?f=%5Cpm%20%5Csqrt%7B7%7D%3Dx%2B1)
![-1\pm \sqrt{7}=x](https://tex.z-dn.net/?f=-1%5Cpm%20%5Csqrt%7B7%7D%3Dx)
![x=-3.646,1.646](https://tex.z-dn.net/?f=x%3D-3.646%2C1.646)
Therefore, the x-intercepts are -3.646 and 1.646. The graph is shown below.